Association of increased oncostatin M with adverse left ventricular remodeling in patients with myocardial infarction: OSM and post-infarction left ventricular remodeling - Gusakova, Anna; Suslova, Tatiana E.; Kercheva, Maria A.; Kologrivova, Irina V.; Ryabova, Tamara R.; Ryabov, Vyacheslav V. (Journal of Medical Biochemistry, 2022)
Background: The study of laboratory biomarkers that reflect the development of adverse cardiovascular events in the postinfarction period is of current relevance. The aim of the present study was evaluation of oncostatin M (OSM) concentration changes in the early and late stages of myocardial infarction and evaluation of the possibility of its use in prediction of adverse left ventricular remodeling in patients with myocardial infarction with ST-elevated segment (STEMI). Methods: The study involved 31 patients with STEMI admitted in the first 24 hours after the onset of MI and 30 patients with chronic coronary artery disease as a control group. Echocardiographic study was performed on day 3 and in 6 months after STEMI. The serum levels of biomarkers were evaluated on the day of hospital admission and 6 months after MI using multiplex immunoassay. Results: OSM level increased during the first 24 h after the onset of the disease, with the following decrease in 6 months. OSM concentration at admission had correlated with echocardiography parameters and Nt-porBNP, troponin I, CK-MB levels. Our study has demonstrated association of the increased levels of OSM at the early stages of STEMI with development of the adverse LV remodeling in 6 months after the event. Conclusion: Elevation of OSM levels in the first 24 h after STEMI is associated with the development of the adverse LV remodeling in the long-term post-infarction period.